E-space Development and its Consequences in the Context of the Non-Marketing-Mix Related Elements of the Marketing Activiies of Organizations - Janusz Wielki (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2008)
This paper is an attempt to present and analyze the impact of e-space on non-marketing- mix elements of marketing activities of organizations. Firstly, definitions of e-space and its basic components are provided i.e. non-Web related space, Web-space and m-space. Next, the attention is focused on each of four pre-marketing-mix elements of marketing activities. So the impact of e-space is analyzed in the context of research, segmentation, targeting and positioning processes. Finally, conclusions are offered.(original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 8, s. 111-119